PARENT NURTURE MODEL IN SHAPING BEHAVIOR OF ADOLESCENCE 12-15 AGES - Dimas Hadi Prayoga; Nursalam Nursalam; Eka Mishbahatul Mar'ah (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2016)
Introduction: The deviation problem of smoking activity an adolescent is come to anxious level for parents, teachers, and society. The correlation between parents nurture model and smoking activity of adolescent needs to be examined further. The purpose of this study was to analyze the correlation between parents nurture model with smoking activity of adolescent (12-15 years old). Method: This was correlational research with cross sectional approach. The sample were 84 adolescent (12-15 years old) at MTs Mojosari Nganjuk. The independent variables was parents nurture model and the dependent variable was adolescent smoking activity. Data were collected by using questionnare, then examined by using chi square with the level of significant α=0,05. Result: Statistical analysis had showed the low correlation between permissive parents nurture model with smoking activity of adolescent (12-15 years old) at MTs Mojosari Nganjuk (p=0,049; r = 0,210) and no correlation between democratic nurture model (p=0,554) and authoritative nurture model (p=0,418) with smoking activity of adolescent (12-15 years old) at MTs Mojosari Nganjuk, but only permissive model which correlate with smoking activity. The permissive parents with no control and demand caused adolescent to be feeling unimpeded to do smoking activity since there is no warning and punishment from the parents. Discussion: So that, School nurses should provide health promotion to parents in making appropriate parenting in adolescence. Parents should have the right parenting provided in accordance with the age and development of adolescents because appropriate parenting will have a positive impact on adolescent behavior. Further research on parenting questionnaires must be checked for cross-compatibility between questionnaire answers given adolescent and parents to know the truth in filling out the questionnaire. The differences in this study compared to previous studies is the researcher doing research in the school semi islamic boarding school, while the previous study examined in formal school.Keywords: parent nurture model, smoking activity, adolescent